Efficiency of Trichome-Based Plant Defense in Phaseolus vulgaris Depends on Insect Behavior, Plant Ontogeny, and Structure - Xing, Zhenlong; Liu, Yongqiang; Cai, Wanzhi; Huang, Xinzheng; Wu, Shengyong; Lei, Zhongren (Frontiers in Plant Science, 2017)
Plant trichomes often function as physical barriers in preventing arthropod feeding and oviposition. Even though insects are frequently reported being entrapped and killed by trichome traps, the actual trapping behavior has not yet been described in detail. Capture experiments showed that capture efficiency during the plant's vegetative stage was considerably higher than in the fruiting and cotyledon stages. The ventral surface of the leaf was more effective in trapping flies than other parts of the plant. Capture-events monitoring showed that the mouthparts, legs, and ovipositor of Liriomyza trifolii adults are the body parts involved in entrapment by surface trichomes on Phaseolus vulgaris plants, and subsequently, deter their ability to feed, walk, and oviposit. Of the three main body parts normally affected, mouthparts was found to be the body part most susceptible to the trichomes. Entrapments were most often caused by landing, followed by puncturing or feeding, and occasionally by walking or fighting. Using scanning electron microscopy (SEM) and optical microscopy, we determined the susceptible positions of each body part and found that the flies were all trapped by hooked trichomes. This study revealed the process by which leafminer flies are entrapped by surface trichomes of the host plant and evaluated the capture efficiency. The results will contribute to our understanding of physical defenses against herbivores.